Ethics of climate engineering: Don't forget technology has an ethical aspect too. (April 2022) - Brooks, Laurence; Cannizzaro, Sara; Umbrello, Steven; Bernstein, Michael J.; Richardson, Kathleen
Abstract: Climate change may well be the most important issue of the 21st century and the world's response, in the form of 'Climate Engineering', is therefore of equal pre-eminent importance. However, while there are technological challenges, there are equally just as important ethical challenges that these technologies also generate. Governments, funding agencies and non-governmental organisations increasingly recognise the importance of incorporating ethics into the development of emerging technologies (for example, within the EU draft legislation on AI). As the world faces the global challenge of climate change there are urgent efforts to develop strategies so that responses to the climate problems do not reproduce more of the same. Ethical values from the onset are fundamental to this process and need highlighting. Hence, this paper analyses a series of ethical codes, framework and guidelines of the new emerging technologies of climate engineering (CE) through a review of both published academic literature and grey literature from either industry, government, and non-governmental (NGO) organisations. This paper was developed as part of a collaboration with international partners from TechEthos (TechEthos receives funding from the EU H2020 research and innovation programme under Grant Agreement No 101006249; Ethics of Emerging Technologies), an EU-funded project that deals with the ethics of the new and emerging technologies anticipated to have high socio-economic impact. Our findings have identified the following ethical considerations including autonomy, freedom, integrity, human rights and privacy in the developmental process of climate engineering, while a poverty of ethical values reflecting dignity and trust were noted. Highlights: Climate change may well be the most important issue of the 21st century. There are technological challenges, and equally as important ethical challenges. Ethical considerations include autonomy, freedom, integrity, human rights and privacy. There are a poverty of ethical values reflecting dignity and trust.